0290 The Antiquities Trade during the German Occupation of France, 1940–1944 - Mattes Lammert (RIHA Journal, 2023)
Despite the confiscation of many art collections, mainly from Jewish families, the Parisian art market was prosperous during the German occupation of France, from 1940 to 1944. This boom was also driven by the vast number of purchases made by German museums. After the war, most of these acquisitions were returned to France, with postwar investigations focusing on the recovery of paintings. The lack of interest in other types of art may explain, at least in part, why the acquisitions made by the Staatliche Museen zu Berlin during the Occupation have been ignored for so long. Mainly antiquities, they are still part of the collections today. As this case study of the holdings of the Ägyptisches Museum in Berlin shows, these acquisitions can serve as a starting point for learning more about the antiquities dealers active during the Occupation.